Perintisan Gereja dalam Konteks Digitalisasi Masa Kini - Simon (STT Bala Keselamatan Palu, 2022)
Abstract: This paper discusses specifically how church pioneering is carried out in a digital context. The urgency of this topic is elaborated considering that in the present day digitalization has been cultivated from various aspects. With today's digital age, the church needs to adapt evangelism according to the context and era in which the church exists. This paper uses the approach of digital religion and literature methods to answer two questions on the topic, how is digitalized religion? And how is the establishment of church that digitalizes? The results of the description on this topic suggest that, the church establishment in a digital context can start from the establishment of a virtual church. Although the virtual church is not in the physical form, religious activities can be felt and experienced by believers through the virtual church. The establishment of the church in a digital context can be done by establishing a virtual communion. The virtual communion serves as a forum to unite people of faith in Jesus. The virtual communion is an alternative to the establishment of digital church. The establishment of digital churches can preserve evangelism as mandated by the Great Commission. Abstrak: Tulisan ini membahas secara spesifik bagaimana perintisan gereja dilakukan dalam konteks digital. Urgensitas topik ini diuraikan mengingat masa kini digitalisasi telah membudaya di berbagai aspek. Dengan zaman digital saat ini, gereja perlu menyesuaikan perintisan sesuai dengan konteks dan zaman dimana gereja berada. Tulisan ini menggunakan pendekatan metode digital dan literatur dengan menjawab dua pertanyaan pada topik, bagaimana tentang agama yang terdigitalisasi? Serta bagaimana penanaman gereja yang meng digital? Hasil uraian pada topik ini mengemukakan bahwa, pengamanan gereja dalam konteks digital dapat dimulai dari pendirian gereja virtual. Walau gereja virtual tidak bersifat fisik, namun aktivitas keagamaan dapat dirasa dan dialami orang percaya melalui gereja virtual ini. Penanaman gereja dalam konteks digital dapat dilakukan dengan membangun persekutuan virtual. Persekutuan virtual sebagai wadah mempersatukan orang yang seiman kepada Yesus. Persekutuan virtual sebagai alternatif dalam penanam gereja secara mendigital. Penanaman gereja secara mendigital melestarikan penginjilan sebagaimana mandata Amanat Agung.